A SELF-HEALTH EMPOWERMENT AND WELLNESS MANAGEMENT APPROACH FOR INDIVIDUALS AGING WITH COMPLEX HEALTH CONDITIONS. (11th November 2018) - Heyn, P C; Tagawa, A; Pan, Z; Carollo, J
Abstract: FiEffective approaches to promote self-health and wellness empowerment for individuals with complex health conditions must be person-focused and multi-disciplinary to be successful. The goal of such program is to support patients and caregivers with decision making power over their health to increase utilization of low cost and accessible community resources to better manage their health. Empowering patients with such self-health management and decision-making tools can have a profound effect on patient's wellbeing and healthspan. We will present an innovative, person-focused self-health management and wellness empowerment program that was evaluated in 70 adults with disabilities who are facing the premature development of chronic diseases and the effects of aging. 60% of the participants reported increased physical activity levels, 57% made positive changes to their diet and 55% showed the health recommendations to a health professional with the goal to involve the health care provider in the self- health management goals.